Performance evaluation of VOIP over WLAN, WIMAX and WLAN-WIMAX integrated network - Abdalla, Abdalla Adam; Abdala, Tarek Mosbah; Dasalla, Valeriano A.; Daud, Nasarudin (2014)
This paper assesses the performance of WLAN and WiMAX networks to carry real time voice traffic communication using the Internet Protocol in a real network, where in the network the voice sessions have to share the link with data, video, and voice.Due to the loose nature of wireless network.Issues like providing QoS at a good level, dedicating capacity for calls is more difficult rather than wired LAN.Therefore VoIP over WLAN and WiMAX remains a challenging research topic.In this paper the Measurements are performed in the WLAN and WiMAX wireless networks. Measurements focus on the three major VoIP parameters: packet loss and jitter.The environmental factors such as the distance between nodes, network traffic, and other obstacles are also considered.Based on the analysis of the findings that have been made, it was discovered that the VoIP application performs better over WiMAX-WiMAX network Than WLAN-WLAN network, In this research experiment, we find out the degradation of those parameters mostly caused by the network condition during the conversation.In order to have the best conversation of VoIP over different wireless networks, the environment as one of the backbone and has to be in a good condition.